2010
DOI: 10.1590/s1516-18462010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo longitudinal da compreensão verbal de crianças usuárias de implante coclear

Abstract: , Maria da Piedade Resende da Costa(3) RESUMOObjetivo: analisar a compreensão verbal de crianças surdas usuárias de implante coclear (IC) por meio de um estudo longitudinal. Métodos: os participantes foram nove crianças surdas usuárias de IC. A idade cronológica das crianças variou entre quatro e oito anos e o tempo de uso do IC foi, em média, 1 ano e 6 meses na 1ª avaliação, 3 anos e 7 meses na 2ª avaliação e 4 anos e 9 meses na 3ª avaliação. [2][3][4][5] . Ele fornece, especi camente, acesso a informações e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
7
0
4
Order By: Relevance
“…28,32,33 However, for this type of intervention to be performed with satisfactory outcomes in the development of auditory and language skills, the hearing diagnosis and speech therapy intervention must be early. 28, 34 Regarding the performance of written language skills in all evaluated groups, the majority of the children had a low performance in the academic achievement test. This result may be associated with low performance in the auditory and oral language tests.…”
Section: Discussionmentioning
confidence: 92%
“…28,32,33 However, for this type of intervention to be performed with satisfactory outcomes in the development of auditory and language skills, the hearing diagnosis and speech therapy intervention must be early. 28, 34 Regarding the performance of written language skills in all evaluated groups, the majority of the children had a low performance in the academic achievement test. This result may be associated with low performance in the auditory and oral language tests.…”
Section: Discussionmentioning
confidence: 92%
“…As crianças surdas podem adquirir todas as habilidades comunicativas, porém por apresentarem um lento progresso no desenvolvimento de habilidades linguísticas, e falta de uma língua em que houve um aumento na compreensão verbal das crianças ao longo do tempo de uso do IC. Dessa maneira, quanto maior o tempo de uso do implante, melhores foram as habilidades de compreensão verbal das crianças 25 . Os mesmos resultados foram encontrados em um estudo que analisou a inteligibilidade de fala de usuários de IC ao longo do tempo.…”
Section: Discussionunclassified
“…In the present review, 26 articles were found 2,6-30 , being eighteen analytical observational transversal studies 2,[6][7][8][9][12][13][14][17][18][19][20][21]23,24,[27][28][29] , four analytical observational longitudinal studies 10,11,16,22 , two reported case 15,25 , one experimental study 26 and one literature review 30 , consisting of nineteen national and seven international researches. The articles were separated in thematic bases and distributed in frames to results presentation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 20 articles that approached oral language 2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] referred to children with diagnosis of hearing loss, but differed on the protocols used to assessment. It is important to highlight that 4 studies of them assessed the communicative abilities 12,14,16,21 , by means of pragmatic protocols (Pragmatic Tasks of ABFW -Teste de Linguagem Infantil, Communicative Abilities Pragmatic Profiles e MAASE linguistic test) or verbal interactions; others four described the language expression and understanding 9,11,13,22 using the Reynell Development Language Scales (RDLS) and there were others four articles that have analyzed the vocabulary 7,18,20,24 by means of different protocols (Vocabulary Tasks of ABFW -Teste de Linguagem Infantil, Peabody Picture Vocabulary Test -PPVT e British Picture Vocabulary Scale -BPVS).…”
Section: Figure 2 -Sinthesys Of the Studies Concerning The Researchs mentioning
confidence: 99%